2012
DOI: 10.1038/nchembio.901
|View full text |Cite
|
Sign up to set email alerts
|

Programmable enantioselective one-pot synthesis of molecules with eight stereocenters

Abstract: We developed an enantioselectively catalyzed tandem synthesis of structurally and stereochemically complex molecules that forms four carbon-carbon bonds and sets eight stereocenters with high regio-, diastereo- and enantioselectivity. It can be programmed to yield different stereoisomers by varying only the order of combination of a common set of reagents and catalysts. We report what is to our knowledge the first synthesis of both enantiomers of a chiral compound using the same chiral catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…[22,146] Another interesting three component reaction using independent dipolar cycloadditions to benzoquinone (45) was recently disclosed by Waldmann and coworkers (Scheme 24). [147] Enantioselective [3þ2] cycloadditions are deployed in a two-directional sense to unite three components, forming up to eight stereocentres. Judicious modification of reaction conditions allowed the control of both chemo-and regioselectivity, which promises access to a wide range of related structures.…”
Section: Independent Reactionsmentioning
confidence: 99%
“…[22,146] Another interesting three component reaction using independent dipolar cycloadditions to benzoquinone (45) was recently disclosed by Waldmann and coworkers (Scheme 24). [147] Enantioselective [3þ2] cycloadditions are deployed in a two-directional sense to unite three components, forming up to eight stereocentres. Judicious modification of reaction conditions allowed the control of both chemo-and regioselectivity, which promises access to a wide range of related structures.…”
Section: Independent Reactionsmentioning
confidence: 99%
“…The quinone oxidation state of the product produced on standing could be verified from 13 C NMR signals for the C=O carbon at 182.4 and 181.9 ppm. 19 We had initially assigned the trans stereochemistry to this product based on the X-ray of 13a. 12 However, the X-ray analysis of 11c ( Figure 6) clearly showed that this cycloadduct had the 1-naphthyl and ester groups in a cis relationship.…”
Section: Resultsmentioning
confidence: 99%
“…[109] This was achieved by engaging benzoquinone (162) in two subsequent dipolar cycloadditions with imines 163, followed by imines 164, in the presence of the phosphane catalyst 165. [109] This was achieved by engaging benzoquinone (162) in two subsequent dipolar cycloadditions with imines 163, followed by imines 164, in the presence of the phosphane catalyst 165.…”
Section: Reagent-based Strategymentioning
confidence: 99%